Exclusive Breastfeeding and Infant Psychomotor Development - Labatjo, Rahma; Saleh, Isma; Blongkod, Fitriani R (Universitas Airlangga, 2023)
Exclusive breastfeeding is known as giving an infant breastmilk for the first six months. Breastmilk is provided to the infant as the only food source, and they will acquire additional food after 6 months of age. Mothers in Indonesia frequently experience an issue related to exclusive breastfeeding. Some of the mothers' perceptions believe that their breastmilk is insufficient, meaning that the mother merely possesses a limited amount of milk. This study seeks to determine the relationship between exclusive breastfeeding and psychomotor development in infants aged 6-9 months in the working area of Buntuila Community Health Center. This study applied a quantitative approach, while data analysis used statistics. It employs analytical observational research,with cross-sectional design. Samples were collected simultaneously. Based on the study findings, infants who were exclusively breastfed experienced normal development were 17 samples (70.8%), questionable development were 7 samples (29.2%), and deviant development by 0 samples (0.0%). While infants who were not exclusively breastfed experienced normal development were 11 samples (35.5%), questionable development were 13 samples (41.9%), and deviant development were 7 samples (22.6). It is undeniable that exclusive breastfeeding has a significant role in infant's psychomotor development. Therefore, it is important to improve multi-stakeholder actions such as health promotion and campaigns on exclusive breastfeeding.